1976
DOI: 10.1161/01.cir.54.5.810
|View full text |Cite
|
Sign up to set email alerts
|

The palliative Mustard operation for double outlet right ventricle or transposition of the great arteries associated with ventricular septal defect, pulmonary arterial hypertension, and pulmonary vascular obstructive disease. A report of eight patients.

Abstract: ' (VSD). This group of patients is seldom severely hypoxemic in infancy, in contrast to babies with an intact ventricular septum, but is at high risk to develop congestive heart failure, pulmonary arterial hypertension (PAH), and pulmonary vascular obstructive disease early in life.6"' Palliation with a pulmonary artery band carries a high mortality,'0 11 and until recently4 11 complete repair in infancy was not possible. In the past most of these patients who were not successfully banded died in congestive he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 22 publications
2
12
0
1
Order By: Relevance
“…In this procedure, patients with transposition of great arteries and a large ventricular communication, in which oxygen saturations in the pulmonary artery are higher than that in the aorta, undergo an atrial switch without VSD closure. 38,39 The increase in arterial oxygen saturation resulting from redirection of flow provides significant symptomatic relief and increased quality of life in patients with severe cyanosis-related symptoms. It has been suggested that treatment with advanced therapies without correction of the underlying anatomical defect may lead to further insult on the pulmonary circulation.…”
Section: Corrective Interventionsmentioning
confidence: 99%
“…In this procedure, patients with transposition of great arteries and a large ventricular communication, in which oxygen saturations in the pulmonary artery are higher than that in the aorta, undergo an atrial switch without VSD closure. 38,39 The increase in arterial oxygen saturation resulting from redirection of flow provides significant symptomatic relief and increased quality of life in patients with severe cyanosis-related symptoms. It has been suggested that treatment with advanced therapies without correction of the underlying anatomical defect may lead to further insult on the pulmonary circulation.…”
Section: Corrective Interventionsmentioning
confidence: 99%
“…6, No . 2,1985 CoA, coarctation procedure ; DKS, Damus, Kaye, Stansel procedure ; PAB, pulmonary artery banding ; d, days ; m, months ; w, weeks ; and y, years .…”
Section: Discussionmentioning
confidence: 99%
“…6, No . 2,1985 arteries, VSD, PDA, and severe CoA were diagnosed . A Rashkind balloon atria] septostomy was performed .…”
Section: Case Reportsmentioning
confidence: 99%
“…[3][4][5] Knowledge about the state and fate in adults is sparse. This study reports the findings in all adults patients seen in the Grown-up Congenital Heart Unit during the past [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (mean (SD) 11 (5.7)) years, 15-20 years after palliative Mustard operation.…”
mentioning
confidence: 99%